Reduced Proactive Control Processes Associated With Behavioral Response Inhibition Deficits in Autism Spectrum Disorder - Kelly, Shannon E. (Autism Res, 2020)
Impairments in inhibitory control are common in individuals with autism spectrum disorder (ASD) and associated with multiple clinical issues. Proactive (i.e., delaying response onset) and reactive control mechanisms (i.e., stopping quickly) contribute to successful inhibitory control in typically developing individuals and may be compromised in ASD. We assessed inhibitory control in 58 individuals with ASD and 63 typically developing controls aged 5–29 years using an oculomotor stop-signal task during which participants made rapid eye movements (i.e., saccades) toward peripheral targets (i.e., GO trials) or inhibited saccades (i.e., STOP trials). Individuals with ASD exhibited reduced ability to inhibit saccades, reduced reaction time slowing (GO RT slowing), and faster stop-signal reaction times (SSRT) compared to controls. Across participants, stopping accuracy was positively related to GO RT slowing, and increased age was associated with higher stopping accuracy and GO RT slowing. Our results indicate that failures to proactively delay prepotent responses in ASD underpin deficits of inhibitory control and may contribute to difficulties modifying their behavior according to changes in contextual demands. These findings implicate frontostriatal brain networks in inhibitory control and core symptoms of ASD.